The Development of Science Learning Model for Higher Education of Bachelor Elementary School Teacher Education Program in Distance Learning - Budiastra, A.A. Ketut; Warsihna, Jaka; Widiasih; Puspitasari, Susy (Advances in Social Sciences Research Journal, 2020)
This research is the second year of a three-year research plan and the development of a new generation of Universitas Terbuka (UT) learning material models for natural science learning courses in elementary schools for higher education of bachelor elementary school teacher education program at the Faculty of Teacher Training and Education. The research design in this research is a combination of the major steps in the R&D cycle with the steps of the system approach to the model of educational R&D. In this research, a series of development and research activities were carried out and is the 8th step of the 15 planned series of activities. The steps in developing the initial format for the New Generation Learning Materials of UT include a series of workshops and independent work. The final product of this research is in the form of nine draft modules consisting of three components, namely: (1) fully printed; (2) blended; and (3) fully online.